The impact of ovarian stimulation on the human endometrial microenvironment - Chemerinski, Anat; Shen, May; Valero-Pacheco, Nuriban; Zhao, Qingshi; Murphy, Trystn; George, Lea; Lemenze, Alex; Sherman, Lauren; Heller, Debra; Chen, Xiaowei; Wu, Tracy; McGovern, Peter G; et al. (Human reproduction (Oxford), 2024)
How does ovarian stimulation (OS), which is used to mature multiple oocytes for ART procedures, impact the principal cellular compartments and transcriptome of the human endometrium in the periovulatory and mid-secretory phases? During the mid-secretory window of implantation, OS alters the abundance of endometrial immune cells, whereas during the periovulatory period, OS substantially changes the endometrial transcriptome and impacts both endometrial glandular and immune cells. Pregnancies conceived in an OS cycle are at risk of complications reflective of abnormal placentation and placental function. OS can alter endometrial gene expression and immune cell populations. How OS impacts the glandular, stromal, immune, and vascular compartments of the endometrium, in the periovulatory period as compared to the window of implantation, is unknown. This prospective cohort study carried out between 2020 and 2022 included 25 subjects undergoing OS and 25 subjects in natural menstrual cycles. Endometrial biopsies were performed in the proliferative, periovulatory, and mid-secretory phases. Blood samples were processed to determine serum estradiol and progesterone levels. Both the endometrial transcriptome and the principal cellular compartments of the endometrium, including glands, stroma, immune, and vasculature, were evaluated by examining endometrial dating, differential gene expression, protein expression, cell populations, and the three-dimensional structure in endometrial tissue. Mann-Whitney U tests, unpaired t-tests or one-way ANOVA and pairwise multiple comparison tests were used to statistically evaluate differences. In the periovulatory period, OS induced high levels of differential gene expression, glandular-stromal dyssynchrony, and an increase in both glandular epithelial volume and the frequency of endometrial monocytes/macrophages. In the window of implantation during the mid-secretory phase, OS induced changes in endometrial immune cells, with a greater frequency of B cells and a lower frequency of CD4 effector T cells. The data underlying this article have been uploaded to the Genome Expression Omnibus/National Center for Biotechnology Information with accession number GSE220044. A limited number of subjects were included in this study, although the subjects within each group, natural cycle or OS, were homogenous in their clinical characteristics. The number of subjects utilized was sufficient to identify significant differences; however, with a larger number of subjects and additional power, we may detect additional differences. Another limitation of the study is that proliferative phase biopsies were collected in natural cycles, but not in OS cycles. Given that the OS cycle subjects did not have known endometrial factor infertility, and the comparisons involved subjects who had a similar and robust response to stimulation, the findings are generalizable to women with a normal response to OS. OS substantially altered the periovulatory phase endometrium, with fewer transcriptomic and cell type-specific changes in the mid-secretory phase. Our findings show that after OS, the endometrial microenvironment in the window of implantation possesses many more similarities to that of a natural cycle than does the periovulatory endometrium. Further investigation of the immune compartment and the functional significance of this cellular compartment under OS conditions is warranted. Research reported in this publication was supported by the National Institute of Allergy and Infectious Diseases (R01AI148695 to A.M.B. and N.C.D.), Eunice Kennedy Shriver National Institute of Child Health and Human Development (R01HD109152 to R.A.), and the March of Dimes (5-FY20-209 to R.A.). The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health or March of Dimes. All authors declare no conflict of interest.